Methylenetetrahydrofolate reductase polymorphisms in acute deep vein thrombosis - Şenol, Sefa; Kargün, Kürşat (My University, 2019)
Objectives: In this study, we aimed to investigate the effectiveness of methylenetetrahydrofolate reductase (MTHFR) C677T andA1298C gene polymorphisms in acute deep vein thrombosis (DVT).Patients and methods: Between January 2017 and May 2018, a total of 64 patients (37 males, 27 females; mean age 35±18 years;range 19 to 59 years) who were followed with the diagnosis of acute DVT and 64 healthy controls (35 males, 29 females; mean age 43±14 years;range 23 to 57 years) without any vascular pathology were included. The MTHFR C677T and A1298C gene polymorphisms of thesamples were identified using the real-time polymerase chain reaction.Results: There was no statistically significant difference in the polymorphisms and allele frequencies of the MTHFR C677T andA1298C genes between the patient and control groups (p>0.05).Conclusion: In this study, the MTHFR C677T and A1298C gene polymorphisms were not found to be risk factors for acute DVT.
Keywords: Periferik Damar Hastalıkları; Tıbbi Araştırmalar Deneysel